Assessing Community Readiness to Convert Waste Cooking Oil (WCO) into Soap in Parit Jelutong, Johor - Malek, Nur Athilah Akma; Roslinda Ali,; Sumaiyah Mashori, (Progress in Engineering Application and Technology, 2026)
Improper disposal of waste cooking oil (WCO) remains a significant environmental issue in Malaysia, particularly at the household and community levels, contributing to drainage blockage and environmental pollution. This study aims to assess the readiness of the Parit Jelutong community in Johor to adopt WCO recycling through soap making activities as a sustainable waste management approach. A quantitative research design was employed and implemented in three stages: pre-implementation, implementation, and post-implementation. Data were collected through structured questionnaires from 73 respondents and analyzed using descriptive statistics and Mann–Whitney U tests. The findings revealed that respondents generally demonstrated a high level of awareness regarding the environmental impacts of improper WCO disposal. However, despite this awareness, actual recycling practices remained limited, indicating a noticeable gap between knowledge and behavioral implementation. Statistical analysis showed a significant difference in 3R awareness between student and non-student respondents, suggesting that non-students possessed higher awareness levels, likely due to greater exposure to real life experiences, workplace practices, community programs, and media engagement. In contrast, no statistically significant difference in 3R awareness was observed between male and female respondents, indicating that gender does not play a meaningful role in influencing awareness related to WCO management. Overall, the community showed strong willingness to participate in WCO recycling programs when supported by proper facilities and guidance. It is recommended that continuous training and improved support systems be implemented to encourage long-term adoption of sustainable WCO management practices.